SEROPREVALENSI TOKSOPLASMOSIS PADA WANITA USIA SUBUR DI PUSKESMAS PAAL X KOTA JAMBI: SEROPREVALENSI TOKSOPLASMOSIS PADA WANITA USIA SUBUR DI PUSKESMAS PAAL X KOTA JAMBI - Hanina Hanina; Humaryanto Humaryanto; Gading Patrick William; Aurora Wahyu Indah Dwi (Universitas Jambi, 2023)
ABSTRACT Toxoplasmosis is a zoonotic disease that is a disease in animals that can be transmitted to humans. This disease is caused by sporozoa known as Toxoplasma gondii (T.gondii). Symptoms of toxoplasmosis are apparent in pregnant women who can cause abortions, stillbirths, or babies born to show signs of toxoplasmosis. In Indonesia, research that studies this is still very limited. Therefore, researchers are interested in conducting this research. This study aims to determine the seroprevalence IgG toxoplasmosis in the fertile women at Paal X Health Center from February to April 2019. There was 22 respondents (42.3%) were have IgG toxoplasmosis positive. Keywords: Seroprevalence, IgG, Toxoplasmosis